Bis(pentalene)di-titanium: A bent double-sandwich complex with a very short Ti-Ti bond - Kilpatrick, Alexander F.R.; Green, Jennifer C.; Cloke, F. Geoffrey N.; Tsoureas, Nikolaos (Chemical Communications, 2013)
The novel bimetallic bis(pentalene) complex Ti2(μ:η5,η5-Pn†)2 (Pn† = C8H4(SiiPr3-1,4)2) has been synthesised and structurally characterised. Structural data show a Ti-Ti distance of 2.399(2) å, consistent with a strong metal-metal interaction, which DFT calculations best describe as a double bond with σ and π components. © 2013 The Royal Society of Chemistry.